prompt
stringlengths
46
55
ground_truth
int64
-10
10
Solve for b in the following equation: 6b + 4 = -32
-6
Solve for c in the following equation: -5c - 6 = -36
6
Solve for z in the following equation: -7z + 9 = 72
-9
Solve for z in the following equation: 9z - 2 = -83
-9
Solve for c in the following equation: -8c + 3 = 83
-10
Solve for b in the following equation: -6b + 10 = 64
-9
Solve for y in the following equation: 2y + 7 = 1
-3
Solve for c in the following equation: 3c + 2 = 20
6
Solve for y in the following equation: -10y + 4 = 84
-8
Solve for c in the following equation: -7c + 5 = 33
-4
Solve for a in the following equation: -9a + 3 = -42
5
Solve for x in the following equation: -3x + 1 = -11
4
Solve for y in the following equation: 3y + 8 = -13
-7
Solve for b in the following equation: -9b + 3 = 21
-2
Solve for x in the following equation: -8x - 10 = -34
3
Solve for a in the following equation: 9a - 2 = -11
-1
Solve for x in the following equation: -6x + 1 = 1
0
Solve for z in the following equation: 1z - 4 = 1
5
Solve for y in the following equation: 3y + 1 = -29
-10
Solve for y in the following equation: -7y + 10 = 45
-5
Solve for b in the following equation: 2b + 9 = 1
-4
Solve for c in the following equation: -8c - 10 = -58
6
Solve for a in the following equation: 5a - 10 = 20
6
Solve for c in the following equation: -2c + 10 = -8
9
Solve for c in the following equation: -9c - 3 = -21
2
Solve for c in the following equation: -9c + 10 = -80
10
Solve for y in the following equation: -3y - 2 = -2
0
Solve for c in the following equation: -7c - 5 = 23
-4
Solve for c in the following equation: 4c - 10 = -38
-7
Solve for y in the following equation: 6y + 8 = 14
1
Solve for z in the following equation: 2z + 1 = -13
-7
Solve for a in the following equation: 6a - 1 = -25
-4
Solve for b in the following equation: 7b + 3 = -32
-5
Solve for x in the following equation: -10x + 6 = 56
-5
Solve for a in the following equation: 6a - 9 = 39
8
Solve for x in the following equation: 5x - 3 = -3
0
Solve for z in the following equation: -5z - 6 = -21
3
Solve for a in the following equation: 2a = 10
5
Solve for z in the following equation: 2z + 7 = -1
-4
Solve for x in the following equation: -4x + 7 = -29
9
Solve for a in the following equation: -2a - 10 = -30
10
Solve for x in the following equation: 5x - 1 = -41
-8
Solve for x in the following equation: -7x + 8 = 1
1
Solve for a in the following equation: 2a + 3 = 3
0
Solve for a in the following equation: 5a - 7 = -47
-8
Solve for a in the following equation: -4a = -8
2
Solve for y in the following equation: -5y - 7 = -7
0
Solve for z in the following equation: 4z + 8 = 4
-1
Solve for z in the following equation: -5z - 9 = 1
-2
Solve for z in the following equation: -3z - 4 = 2
-2
Solve for z in the following equation: 10z - 7 = 53
6
Solve for z in the following equation: 6z + 6 = 54
8
Solve for c in the following equation: -9c - 4 = 23
-3
Solve for b in the following equation: -6b - 5 = 19
-4
Solve for b in the following equation: -9b + 8 = 35
-3
Solve for z in the following equation: 9z + 9 = 63
6
Solve for z in the following equation: -7z + 5 = 40
-5
Solve for a in the following equation: 8a + 2 = 66
8
Solve for a in the following equation: 9a - 7 = -34
-3
Solve for b in the following equation: -4b + 6 = 10
-1
Solve for b in the following equation: 10b = -20
-2
Solve for x in the following equation: 10x + 1 = -59
-6
Solve for a in the following equation: 2a - 10 = 6
8
Solve for y in the following equation: 8y - 6 = 18
3
Solve for b in the following equation: -3b = -21
7
Solve for z in the following equation: 5z + 9 = 9
0
Solve for y in the following equation: -2y + 9 = 15
-3
Solve for z in the following equation: -6z - 1 = -25
4
Solve for y in the following equation: 5y = -20
-4
Solve for c in the following equation: -1c - 2 = -12
10
Solve for a in the following equation: -7a + 4 = -52
8
Solve for z in the following equation: 1z - 7 = 2
9
Solve for z in the following equation: 5z - 3 = 2
1
Solve for c in the following equation: 5c + 7 = -33
-8
Solve for c in the following equation: 2c + 8 = -2
-5
Solve for y in the following equation: 3y + 6 = 6
0
Solve for a in the following equation: -6a - 6 = -48
7
Solve for b in the following equation: -1b - 2 = -7
5
Solve for x in the following equation: -10x + 8 = 68
-6
Solve for y in the following equation: -3y - 4 = -19
5
Solve for z in the following equation: -9z - 10 = 71
-9
Solve for x in the following equation: 9x - 4 = -67
-7
Solve for a in the following equation: -6a + 3 = -21
4
Solve for x in the following equation: -7x + 3 = -46
7
Solve for y in the following equation: 2y - 2 = -10
-4
Solve for b in the following equation: -10b + 5 = 85
-8
Solve for y in the following equation: -5y + 9 = -26
7
Solve for x in the following equation: -6x + 3 = -9
2
Solve for c in the following equation: 7c = -42
-6
Solve for c in the following equation: 8c - 6 = -46
-5
Solve for z in the following equation: -10z = 40
-4
Solve for y in the following equation: -3y + 8 = -19
9
Solve for c in the following equation: 7c + 8 = 78
10
Solve for x in the following equation: 10x = -80
-8
Solve for z in the following equation: -4z - 6 = 30
-9
Solve for a in the following equation: 4a - 5 = 35
10
Solve for z in the following equation: -1z - 1 = 2
-3
Solve for y in the following equation: -3y - 5 = 4
-3
Solve for c in the following equation: -1c + 4 = 13
-9
Solve for c in the following equation: -10c + 2 = 92
-9